Evaluasi Kinerja Generator Microbubble Terhadap Kondisi Nutrisi dan Respon Pertumbuhan Kailan (Brassica Oleraceae) Secara Hidroponik Sistem DFT Di Dalam Greenhouse - Habib Ihza Mahendra; Iswahyono Iswahyono; Siti Djamila; Amal Bahariawan; Meta Fitri Rizkiana (Politeknik Negeri Jember, 2023)
The kailan plant (Brassica oleraceae) has high commercial potential due to its high nutritional content, delicious taste, and high market interest. Kailan could be cultivated through hydroponic planting by utilizing limited land. The DFT hydroponic system is an option due to faster and constant growth, shorter harvest period, and easy maintenance. If the power goes out, the plants can still survive. One of the weaknesses is the limited oxygen availability due to poor circulation. This study aimed to determine the effect of using a microbubble generator to enrich oxygen on nutritional conditions and the growth response of kailan plants compared to plant growth without a microbubble generator. The applied method in this study was to compare nutritional content and plant growth responses between using a microbubble generator and without utilizing a microbubble generator. The results showed that using the microbubble generator affected nutrients' concentration, temperature, and pH and positively impacted plant growth responses: number of leaves, root condition and plant weight at harvest period.